At the vanguard: Leaders' perspectives on establishing healthcare system infection prevention programs. Issue 1 (9th December 2022) - Stevens, Michael P.; Wright, Sharon B.; Kaye, Keith S.; Zuckerman, Jerry M.; Passaretti, Catherine L.; Martinello, Richard A.; Babcock, Hilary M.; Edmond, Michael B.; Snyder, Graham M.
Abstract: Hospitals are increasingly consolidating into health systems. Some systems have appointed healthcare epidemiologists to lead system-level infection prevention programs. Ideal program infrastructure and support resources have not been described. We informally surveyed 7 healthcare epidemiologists with recent experience building and leading system-level infection prevention programs. Key facilitators and barriers for program structure and implementation are described.